A keyless secure data aggregation mechanism. (17th November 2019) - Kumar, Sunil; Singh, Karan
Abstract: Now days, mobile sensing system is known as a hand-held as a computer which has full of many properties to run the applications. The important fact is that sensor gave a platform to smart-phones or mobile sensing devices, which are attracting attention towards next innovation in social networks, green technologies, local and global environmental monitoring, sensing enabled games, transportation systems, government, private as well as social health care etc. The mobile sensing system infrastructure is as a part of a new sensing prototype leveraging humans that study the security issues and develop the timeserving people-centric sensing. This paper tackles the problem of mobile sensing system related to security issue. The proposed work is improving the secure data aggregation mechanism which is based on encryption and decryption mechanism of sensing of data with aggregation. The research work is implemented in Java technology. Results and discussion with comparison are also part of this work.